Throughput limits of two 802.15.4 wireless networks applications for signal acquisition - Alves, Joel (2011)
This work describes the development and test of a wireless sensor network used by a biomedical signal monitoring system. Data communication is based on a body area network (BAN) materialized as a wireless network in two versions, one based on the 802.15.4 specification and another on a higher-level Zigbee protocol. The system was developed using the Jennic JN5148 microcontroller, Jennics ZBPro stack and the JenOs RT kernell. The final system was tested with the devices at different distances, and with a varying number of sensor nodes communicating simultaneously. For each of these combinations the signal quality and frequency of communication errors were recorded. The version implemented using Zigbee protocol was able to acquire and send sensor signals at a sample rate of 7 kSamples/s (12-bit samples, final net rate of 84 kbps) with a percentage of lost frames below 4%. It was also shown that the system supports simultaneous communication of three sensor nodes at 3 kS/s (36 kbps) each, with a percentage of losses of less than 4%. These results are important since they support the possibility of having several sensors acquiring fast biomedical signals and sending them to a central unit in real time.